Pengaruh Relaksasi Otot Progresif terhadap Nyeri dan Tekanan Darah pada Penderita Hipertensi - Almana Hithah Irli; Indah Sri Wahyuningsih; Mohammad Arifin Noor (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
One of the health issues that can lead to significant consequences, including heart disease and organ damage, is hypertension. For hypertensive patients, non-pharmacological treatments such as progressive muscle relaxation (PMR) offer an alternative to reduce discomfort and blood pressure. This study uses a quantitative methodology and a quasi-experimental design. For two weeks, 66 hypertensive patients from Puskesmas Bangetayu Semarang participated in the ROP intervention. The T-Test and Wilcoxon statistical tests were used to measure blood pressure and pain levels before and after the intervention. According to the Numeric Rating Scale (NRS), ROP therapy reduced pain from 2.68 to 1.76 and systolic blood pressure from an average of 150.15 mmHg to 133.64 mmHg. With a p-value of less than 0.05, statistical analysis revealed a significant difference. It has been proven that progressive muscle relaxation helps hypertensive individuals with their pain and blood pressure. This approach can be used both independently and in healthcare settings as a simple and safe non-pharmacological treatment. the effect of progressive muscle relaxation on pain and blood pressure in hypertensive patients